A History of the Book in America : Volume 3: The Industrial Book, 1840-1880 - Casper, Scott E. (Book collections on Project MUSE., 2007)
This volume of A History of the Book in America covers the creation, distribution, and uses of print and books in the mid-nineteenth century, when a truly national book trade emerged. Essays examine the rise of the manufactured, bound product and the idea of the book as the quintessential product of the industrialization of both the print and papermaking trades, which depended on new nationwide networks for finance, transportation, and communication. The volume also chronicles the rise of a uniquely American print culture, as reading and writing were increasingly conceived of as essential to A.